The ghost war - Berenson, Alex (New York : Jove Books, 2009)
Returning to Washington after a harrowing case in the Middle East, CIA agent and al-Qaeda infiltrator John Wells is selected to investigate a surge in Taliban activity with possible Asian ties.
National College of Business and Arts
Keywords: Intelligence service -- Fiction; Suspense fiction